Symptomatic psychopathological dimensions in Metropolitan Lima drivers - Ponce Díaz, Carlos (2015)
The objective of this study was to describe and compare the symptomatic psychopathological dimensions in private drivers, private service, and public service providers in Metropolitan Lima. The participants were 1,985 male drivers between the ages of 18 and 76. The instrument used was the Symptoms Checklist 90 Revised (SCL-90-R), by L. R. Derogatis that measures three global indexes and 10 specific symptomatic dimensions. The results reveal that the private and public service drivers show particular indicators of global psychical and psychosomatic suffering, as well as, a greater number of symptoms and diversity of psychopathologies; a greater symptomatic intensity average, and elevated indicators in the majority of specific psychopathological dimensions. Also, it was found that among the public service drivers, the motorcycle-taxi and minibus-drivers, coupled with the particular drivers, infer in the highest incidence of global and specific symptomatic psychopathological dimensions, compared with their peers who provide school mobility, taxi drivers, truckers, urban and interprovincial bus drivers, who record low values in these indicators.